Using of Exact Queries and Expansion Queries in Searching for Indonesian Translated Al-Quran Verses - Rusydi Umar; Ihyak Ulumuddin (Institute of Computer Science (IOCS), 2020)
This paper presents a search technique for translating verses in the Al-Quran into Indonesian by developing a query expansion of the hot themes currently being discussed in social media. The hope of finding information in the verses of the Koran is very high as a step to respond and find a holistic religious perspective on the theme being discussed. The method of searching for verses using Indonesian translations is still deemed inadequate. The availability of dictionaries and indexes for the Indonesian translation of the Al-Quran is still very little, most of the verse search indexes use the Arabic book language including the very popular ones are Al-Mu'jam al-Mufahras lialfazhi Al-Qur'an and Fathurrahman li Thalibi Ayatil Qur'an. Researchers have carried out many studies to make certain techniques in searching to find related words in the Al-Quran, including from exact matching, matching according to major themes in the Koran (topic matching), matching with synonyms and a search for explanatory books (tafsir matching). This is done to find relevant verses and provide comprehensive information on the search terms. This research was conducted on 11 random keywords to the entire translation of the Al-Quran and the query results were tested based on the Al-Quran Index Book How to Find Al-Quran Verses compiled by N.A. Baiquni. HE. S Compoundqi, and R.A. Azis. The results of this study indicate that the use of query expansion gets a value of 44% and the exact query gets a value of 33% to find related themes, however the use of query expansion is better than the use of exact queries in the search for the translation of the Indonesian Al-Quran.